Analisis Signifikansi Pendekatan dalam Studi Islam - Rais Nusi, Suwarin; Caco, Rahmawati (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This article analyzes the significance of approaches in Islamic studies in order to broaden insight and boost the scientific stagnation of the people, especially in terms of approaches to Islamic studies in Indonesia. This research is a type of library research. Literature study is a data collection technique by conducting a review study of books, literature, notes and reports that are related to the problem being solved. The stages that researchers must take in library research are: First, collecting research materials. The material collected is in the form of empirical data sourced from books, journals, results of official and scientific research reports and other literature that supports the theme of this research. Second, read library material. In reading research materials, readers must dig deeply into the reading material which will enable them to find new ideas related to the research title. Third, make research notes. Fourth, processing research notes. All material that has been read is then processed or analyzed to obtain a conclusion which is prepared in the form of a research report. Data analysis is the process of simplifying data into a form that is easy to read and interpret. In this research, after collecting data, the data is analyzed to obtain conclusions. The form of technique for analyzing this data is content analysis. The results of the research, as well as the results of theoretical studies, the author found that the significance of the Islamic study approach in building religious understanding is the approaches that can be used in Islamic studies, namely theological, normative, anthropological, sociological, philosophical, historical, cultural, psychological and doctrinal approaches.